Efektivitas Model Learning Cycle 5E dengan Teknik Make a Match Terhadap Hasil Belajar Peserta Didik Kelas XI MIPA 3 SMA Negeri 6 Bone - Wardani H. Abidin; Muharram Muharram; Netti Herawati (ChemEdu, 2023)
This research is a descriptive research that aims to determine the effectiveness of the 5E learning cycle model with the make a match technique on the learning outcomes of students in class XI MIPA SMA Negeri 6 Bone on the subject matter of acids and bases. The research was conducted by giving a pretest before treatment and giving a posttest after treatment. The subject of this research is class XI MIPA 3 which consists of 36 students. Data were collected using learning outcomes tests and observation sheets which were analyzed descriptively. The results of the study are: (1) Class completeness of students achieved is 83.33%. (2) The average value of normalized gain in learning outcomes of students is 0.78 which is in the high category. (3) The average activity of students in the learning process is 91.49% and is in the very good category. Based on normalized gain, it can be concluded that the application of the 5E learning cycle model with the make a match technique is effective on the learning outcomes of students of class XI MIPA SMA Negeri 6 Bone on the subject matter of acids and bases.